COMPARISON of BMI and HbA1c 3 MONTHS POST ROUX-EN-Y GASTRIC BYPASS and SLEEVE GASTRECTOMY at SUMBER WARAS HOSPITAL JAKARTA - Julia Clairine Setyadi; Jeffrey Jeffrey (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Obesity is a chronic condition that is closely linked to type 2 diabetes mellitus. Bariatric surgery is deemed to be an effective method to reduce weight and induce diabetes remission. Laparoscopic Roux-en-Y Gastric Bypass (RYGB) and laparoscopic Sleeve Gastrectomy (SG) are the most commonly performed surgical procedures. Objective: This study aimed to find out the efficacy of bariatric surgery including the more effective method between Roux-en-Y Gastric Bypass and Sleeve Gastrectomy in lowering BMI and improving HbA1c levels. Methods: This study is a cohort retrospective study of 64 patients who underwent laparoscopic RYGB  and SG in January 2020 – September 2023 in Sumber Waras Hospital. Data regarding BMI and HbA1c pre- and 3 months post-surgery were collected and analyzed using SPSS with statistical significance defined as p <0.05. Results: Greater decrease of IMT (p=0,000) and HbA1c (0,013) were observed in patients post laparoscopic RYGB. Meanwhile, in morbidly obese patients (BMI pre-op > 35kg/m2), no significant differences were found in HbA1c changes in both groups (p=0,240).  Conclusion: Laparoscopic RYGB is more effective in lowering BMI and HbA1c compared to laparoscopic SG. However, this comparison does not apply in morbidly obese patients.